Virulence determinants and the global regulation of virulence in Xanthomonas campestris - Vojnov, A. A; Dow, J. M; Bouarab, K (Molecular Plant-Microbe Interactions, 2009)
pathovar ( ) is the causal agent of black rot disease of cruciferous plants. The ability of to elicit disease depends upon the synthesis of a number of factors, including the extracellular polysaccharide xanthan, extracellular plant cell wall degrading enzymes and cyclic glucan, as well as the formation of biofilms. The synthesis of these extracellular virulence factors is subject to coordinated control by genes within the gene cluster. Some of these genes encode elements of a cell-cell signalling system mediated by the diffusible signal factor (DSF), which is an unsaturated fatty acid. Here we review current progress on our understanding of the roles of xanthan, cyclic glucan and biofilm development in the interaction of with plants, and of the mechanistic basis of regulation of these processes by DSF. New roles for xanthan and cyclic glucan in disease, through the suppression of plant immune responses, have been uncovered. Xanthan induces susceptibility to in and by suppressing basal defences such as callose deposition. Unlike xanthan, which acts only locally, the effects of cyclic glucan on plant defence suppression and callose deposition occur in a systemic fashion. Xanthan is also involved in biofilm formation by . A fine balance of DSF signalling is required for the formation of structured biofilms in static cultures in minimal medium and for virulence to plants. Recent observations have shown that the perception of the DSF signal requires the sensor kinase RpfC and is linked to the degradation of the intracellular second messenger bis-(3-5)-cyclic di-guanosine monophosphate (cyclic di-GMP) by the HD-GYP domain regulator RpfG. The mechanisms by which cyclic di-GMP exerts its regulatory influence on xanthan, cyclic glucan and biofilm formation remain unclear.